GAMBARAN BENTUK DUKUNGAN KELUARGA AGAR LANJUT USIA SEJAHTERA: STUDI FENOMENOLOGI - Maria theresia arie lilyana; Anindya Arum Cempaka (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2026)
Introduction: The increasing number of elderly people occurs due to high life expectancy, so that issues arise about the welfare of the elderly due to the physical changes they experience. The family has an important role in this matter, so that the quality of life of the elderly in terms of physical, mental and social is achieved. Objective: The purpose of this study is to determine the description of the form of family support for the elderly to achieve subjective well-being in their lives. Method: Qualitative research is used to explore the experiences of the elderly about the form of support received from the family. 12 respondents participated in this study. Interviews with question guides, followed by Colaizzi Analysis obtained themes as a result of the study. Results: 2 themes of this study are: forms of family support for the elderly to be prosperous and factors causing the elderly to feel unwell. Support for the elderly is obtained in the form of attention and living together. The factor causing the elderly to feel unwell is not being involved in family activities. Conclusion: Family support is obtained by the elderly in the form of attention from family members who care for them. The obstacle experienced by the elderly to feel well-being is not being involved in family life because of fear of injury. Therefore, motivation for families to increase support is useful for improving the welfare of the elderly.